The Dark Dream - "Hinton, Nigel" (Puffin Books: London, 1997)
In this fourth Beaver Towers adventure, Philip and old Mr Edgar set off on their travels so that Philip can learn how to use his powers to fight evil. But while they're away, the island itself is under threat. Can Baby B and Nick save the day?
Keywords: Adventure stories